Quantum Chemistry Calculations on Binding Energies and Orbital Localization of Excitons in Organic Photovoltaic Semiconductors - Cao, Hui; Zhang, Chaozhi; Feng, Tiancheng; Chen, Jingjing; Fei, Chenbo; Song, Mingxia (Asian Journal of Chemistry, 2013)
The first principle quantum chemistry calculations is used to investigate the binding energies of excitons and the corresponding orbtial localization of electron and hole in a couple of organic electron donors and electron acceptors. In our calculations, HOMO and LUMO orbitals are exchanged to construct the density matrix and use the quadratically covergent self consistent field method to get the final electronic structures of excitons. Our calculated binding energies of the selected systems are 0.3-0.6 eV, in good agreement with the experiments. The orbital localization of electron and hole in excition compared with the ground state is evidently shown with our calculations.